2009
DOI: 10.1097/shk.0b013e31818ba4c6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Postinjury Multiple Organ Failure Scores

Abstract: Most multiple organ failure (MOF) scores were developed over a decade ago, but little has been done in terms of validation and to understand the differences between populations identified by each of them. Given the lack of a gold standard, validation must rely upon objective clinical and resource utilization outcomes. Thus, we propose to: 1)validate two widely accepted MOF scores (Denver's and Marshall's) examining their association with adverse outcomes in a postinjury population; and 2) compare risk factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 41 publications
(39 reference statements)
2
107
0
1
Order By: Relevance
“…12 Moreover, nontherapeutic laparotomy has been associated with a morbidity rate up to 22%, 3 may aggravate patients' conditions, and may delay further evaluation. In the difficult clinical scenario of suspected intra-abdominal sepsis systematic CT scan may increase the physician's level of diagnostic certainty, rule out significant disorders by associating chest or other organ focused CT scan to the abdomino-pelvic scan, and provide an alternative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, nontherapeutic laparotomy has been associated with a morbidity rate up to 22%, 3 may aggravate patients' conditions, and may delay further evaluation. In the difficult clinical scenario of suspected intra-abdominal sepsis systematic CT scan may increase the physician's level of diagnostic certainty, rule out significant disorders by associating chest or other organ focused CT scan to the abdomino-pelvic scan, and provide an alternative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinicians have rightfully focused on correspondence among head, chest, and abdominal injury with MOF, few studies have evaluated the impact and severity of pelvic trauma on the development of MOF [16,23]. ISS has long been used as a surrogate of mechanical injury; however, it has been shown to consistently underestimate mechanical injury [4,25].…”
Section: Discussionmentioning
confidence: 99%
“…Both outcome instruments have been validated in a trauma population [1,9,23]. MOF was described as a score of C 4 with involvement of at least two organ systems for the Denver score [23,24]. The SOFA score evaluates the following six organ systems with an increasing score of dysfunction from 0 to 4: cardiovascular, respiratory, hepatic, renal, hematologic, and neurologic; the Denver MOF score evaluates the following four organ systems with an increasing score of dysfunction from 0 to 3: cardiac, pulmonary, hepatic, and renal ( Table 1).…”
Section: Variables Outcome Measures Data Sources and Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria should include reliability, validity and the ability of a scoring system to unmask temporal changes in organ dysfunction if measured sequentially [18,19]. Studies evaluated the comparative prognostic value of the commonly used organ dysfunction scoring systems concluded that some standardization of the included variables is needed before introducing a scoring tool in everyday practice [20,21]. In the absence of a gold standard scoring or tool for diagnosis or prediction of MODS, validation is required to evaluate the association of different scores with objective, adverse outcomes, clinical status and resource utilization.…”
Section: Scoring and Criteriamentioning
confidence: 99%